Solar-to-supersolar sodium and oxygen absolute abundances for a 'hot Saturn' orbiting a metal-rich star. Issue 2 (7th June 2022) - Nikolov, Nikolay K; Sing, David K; Spake, Jessica J; Smalley, Barry; Goyal, Jayesh M; Mikal-Evans, Thomas; Wakeford, Hannah R; Rustamkulov, Zafar; Deming, Drake; Fortney, Jonathan J; Carter, Aarynn; Gibson, Neale P; et al.
ABSTRACT: We present new analysis of infrared transmission spectroscopy of the cloud-free hot-Saturn WASP-96b performed with the Hubble and Spitzer Space Telescopes ( HST and Spitzer ). The WASP-96b spectrum exhibits the absorption feature from water in excellent agreement with synthetic spectra computed assuming a cloud-free atmosphere. The HST-Spitzer spectrum is coupled with Very Large Telescope (VLT) optical transmission spectroscopy which reveals the full pressure-broadened profile of the sodium absorption feature and enables the derivation of absolute abundances. We confirm and correct for a spectral offset of Δ R_p/R_* =(-4.29^+0.31_-0.37) × 10^-3 of the VLT data relative to the HST-Spitzer spectrum. This offset can be explained by the assumed radius for the common-mode correction of the VLT spectra, which is a well-known feature of ground-based transmission spectroscopy. We find evidence for a lack of chromospheric and photometric activity of the host star which therefore make a negligible contribution to the offset. We measure abundances for Na and O that are consistent with solar to supersolar, with abundances relative to solar values of 21^+27_-14 and 7^+11_-4, respectively. We complement the transmission spectrum with new thermal emission constraints from Spitzer observations at 3.6 and 4.5 μ m, which are best explained by the spectrum of an atmosphere with a temperature decreasing with altitude. A fit to the spectrum assuming an isothermal blackbody atmosphere constrains the dayside temperature to be T p = 1545 ± 90 K.